Functional Food Development of Natural Colorant Additives from Mulberry Fruit Extract (Morus nigra L) with Bioactive and Hedonic Evaluation: Natural Food Colorant from Mulberry Fruit - Yuyun Yuniati; Ratna Yulianti Wijaya; Lidwina Angelica Soetantijo; Juliana; Renny Indrawati (Food Science and Technology Journal (Foodscitech), 2023)
All modern lifestyles such as unhealthy eating patterns and lack of exercise can trigger the accumulation of free radicals in the human body, where the human body cannot neutralize these free radicals fast enough because of the large number of free radicals that have accumulated in it. Therefore, antioxidant compounds need to be consumed to suppress free radicals. In this study, mulberry is promoted as a natural, functional, and dye source that has been explored for further applications in food and beverages. This research aims to develop natural coloring products from mulberry fruit through extraction and encapsulation processes. Furthermore, hedonic testing was also carried out to determine the panelist's preference level for jelly products using mulberry fruit dyes. Mulberry fruit is extracted, encapsulated by freeze drying method, and processed into a natural dye in jelly products. Mulberry fruit extract contains vitamin C 4.1 g/ml, anthocyanin content of 215.16 mg/L, and antioxidant activity of 73.25. Mulberry encapsulates can be used as a natural dye in jelly products. Based on hedonic testing, jelly products made from natural dyes have superior taste and texture. Further development of natural mulberry fruit encapsulated dyes needs to be done to increase solubility, color sharpness, aroma and color stability